Adoption of RRR for improved sanitation in developping countries - CGIAR Research Program on Water, Land and Ecosystems (2017)
IWMI developed a technology for recycling fecal sludge and business models to sustain RRR. The technology is being scaled in Ghana (2 sites) to improve sanitation and generate profits (through increased yields) and jobs. IWMI also tests business models for treated wastewater-based aquaculture and solid wastes based fuel briquette.